2022
DOI: 10.1186/s12966-022-01290-4
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-measured physical activity and sedentary time among children and their parents in the UK before and after COVID-19 lockdowns: a natural experiment

Abstract: Background Restrictions due to the coronavirus disease 2019 (COVID-19) pandemic reduced physical activity provision for both children and their parents. Recent studies have reported decreases in physical activity levels during lockdown restrictions, but these were largely reliant on self-report methods, with data collected via unrepresentative self-report surveys. The post-pandemic impacts on children’s activity levels remain unknown. A key question is how active children become once lockdown r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 32 publications
0
60
2
Order By: Relevance
“…While public health measures offered protection from COVID-19 transmission, parents indicated that the protocols negatively impacted their children's health behaviours. Consistent with local [28], national [9,29] and international findings [13,[30][31][32], many parents reported their children's physical activity declined during the COVID-19 pandemic; the change in activity levels was primarily credited to the loss of organized activities and limited physical activity opportunities. To meet the government's health and safety measures, recreational facilities were either closed or were running at low capacity, disrupting children's regular afterschool programming [33].…”
Section: Discussionmentioning
confidence: 66%
“…While public health measures offered protection from COVID-19 transmission, parents indicated that the protocols negatively impacted their children's health behaviours. Consistent with local [28], national [9,29] and international findings [13,[30][31][32], many parents reported their children's physical activity declined during the COVID-19 pandemic; the change in activity levels was primarily credited to the loss of organized activities and limited physical activity opportunities. To meet the government's health and safety measures, recreational facilities were either closed or were running at low capacity, disrupting children's regular afterschool programming [33].…”
Section: Discussionmentioning
confidence: 66%
“…Note. Qualitative results are displayed in green; the reduction in MVPA reported by Salway and colleagues [ 14 ] is displayed in yellow …”
Section: Resultsmentioning
confidence: 98%
“…Due to the impact of extended periods of social disconnection, children experienced significant emotional overwhelm and fatigue when they were eventually able to reengage with a society that more closely represented a pre-pandemic normality. This led to avoidance of physical activity, particularly unstructured active play, which provides explanation for the observed decrease in MVPA and increase in sedentary time among children who participated in Active-6 [ 14 ]. The narrative relating to changes to active play within two recent qualitative studies were mixed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations